Review: Hubert Knoblauch, Bernt Schnettler, Jürgen Raab & Hans-Georg Soeffner (Eds.) (2006). Video Analysis: Methodology and Methods. Qualitative Audiovisual Data Analysis in Sociology - Jane Reeves (Forum: Qualitative Social Research, 2010)
This book offers the reader a positive overview of the theory and application of this visual sociological technique of video analysis which undoubtedly has a place in our highly visual and technical world. KNOBLAUCH et al. emphasise in this book that video analysis offers the researcher the opportunity to explore and record "natural" ethnographic data whereby the recordings are made in situations affected as little as possible by the researchers. The authors argue that video analysis offers contemporary researchers a unique opportunity to add a further dimension to their work. The book not only offers the reader the opportunity to consider theoretical approaches to this form of analysis, but also offers technical scenarios for the reader to consider in a variety of differing contexts. URN: urn:nbn:de:0114-fqs100267